Assessment of the sensitivity and specificity of Xpert MTB/RIF assay as an early sputum biomarker of response to tuberculosis treatment - Friedrich, Sven O; Rachow, Andrea; Saathoff, Elmar; Singh, Kasha; Mangu, Chacha D; Dawson, Rodney; Phillips, Patrick Pj; Venter, Amour; Bateson, Anna; Boehme, Catharina C; Heinrich, Norbert; Hunt, Robert D; et al. (The lancet respiratory medicine, 2013)
An accurate biomarker is urgently needed to monitor the response to treatment in patients with pulmonary tuberculosis. The Xpert MTB/RIF assay is a commercially available real-time PCR that can be used to detect Mycobacterium-tuberculosis-specific DNA sequences in sputum samples. We therefore evaluated this assay with serial sputum samples obtained over 26 weeks from patients undergoing treatment for tuberculosis. We analysed sputum samples from 221 patients with smear-positive tuberculosis enrolled at two sites (Cape Town, South Africa, and Mbeya, Tanzania) of a multicentre randomised clinical trial REMoxTB of antituberculosis treatment on a weekly basis (weeks 0 to 8), then at weeks 12, 17, 22, and 26 after treatment initiation. The Xpert MTB/RIF results over time were compared with the results of standard smear microscopy and culture methods. We obtained and analysed 2741 sputum samples from 221 patients. The reduction in positivity rates with Xpert MTB/RIF were slower than those with the standard methods. At week 8, positive results were obtained for 62 (29%) of 212 sputum samples with smear microscopy, 46 (26%) of 175 with solid culture (Löwenstein-Jensen medium), 77 (42%) of 183 with liquid culture (Bactec MGIT960 system), and 174 (84%) of 207 with Xpert MTB/RIF; at 26 weeks, positive results were obtained for ten (5%) of 199, four (3%) of 157, seven (4%) of 169, and 22 (27%) of 83 sputum samples, respectively. The reduction in detection of quantitative M tuberculosis DNA with Xpert MTB/RIF correlated with smear grades (ρ=-0·74; p<0·0001), solid culture grades (ρ=-0·73; p<0·0001), and time to liquid culture positivity (ρ=0·73; p<0·0001). Compared with the combined binary smear and culture results as a reference standard, the Xpert MTB/RIF assay had high sensitivity (97·0%, 95% CI 95·8-97·9), but poor specificity (48·6%, 45·0-52·2). The poor specificity precludes the use of the Xpert MTB/RIF assay as a biomarker for monitoring tuberculosis treatment, and should not replace standard smear microscopy and culture. Global Alliance for TB Drug Development, Bill & Melinda Gates Foundation, UK Medical Research Council, German Ministry of Science and Technology.